Penyusunan Katalog Literatur Bahasa Arab Bagi Mahasiswa Pendidikan Bahasa Arab STAIN Mandailing Natal - AULIA RAHMAN (Jurnal Mitra Prima, 2023)
The purpose of this service is to find out the availability of Arabic literature in the STAIN Mandailing Natal library and the creation of a catalog of Arabic literature. This research uses the Community Bassed Research (CBR) method based on the needs of students in obtaining a catalog of Arabic literature and their activities in the Library. The data collection method used in this service is through observation and documentation studies. In addition, data analysis using literature analysis and data reduction. The data taken is Arabic literature in the Library. From the results of this service, the results were obtained that the STAIN Mandailing Natal Library has the availability of Arabic literature so that the preparation of a catalog of Arabic literature is very necessary